Global Glomerulosclerosis and Segmental Glomerulosclerosis Could Serve as Effective Markers for Prognosis and Treatment of IgA Vasculitis With Nephritis - Tan, Jiaxing; Xu, Yicong; Jiang, Zheng; Pei, Gaiqin; Tang, Yi; Tan, Li; Zhong, Zhengxia; Tarun, Padamata; Qin, Wei (Frontiers in Medicine, 2020)
Background: This study was aimed at investigating the clinical significance and curative effect of global glomerulosclerosis (GS) and segmental glomerulosclerosis (S) in adult-onset IgA vasculitis with nephritis (IgAV-N) patients since there was no consensus pathological grading method for adult IgAV-N. Methods: A total of 188 biopsy-proven IgAV-N patients were prospectively identified. Patients were separately assigned to GS0/GS1/GS2 group and S0/S1/S2 based on the scores of global glomerulosclerosis and segmental glomerulosclerosis (0% /0-15% />15%, respectively). Results: GS0, GS1 and GS2 occurred in 56.4%, 29.2% and 14.4% of the adult-onset IgAV-N, respectively. Patients in GS2 group tended to have the most serious renal deterioration and the highest levels of blood pressure. IgAV-N patients were also divided into S0 group (64.4%), S1 group (20.7%) and S2 group (14.9%), where no obvious differences in baseline data were noted. K-M curves indicated that GS2 group had the worst renal outcome (P=0.05) while there seemed to be no significant differences between GS0 group and GS1 group. In addition, no remarkable differences in primary outcome were found among S0 group, S1 group, and S2 group though the prognosis of S2 group tended to be the worst. However, the prognosis of S0/S1 group was markedly better than that of S2 (P=0.04). The discrimination of poor prognosis could be improved by adding the pathological indicators of global glomerulosclerosis and segmental glomerulosclerosis. Most importantly, immunosuppressive treatment might be a superior alternative in IgAV-N patients without sclerosis scores or with lower level of sclerosis scores. But addition of immunosuppression was not recommended in patients with higher sclerosis scores. Conclusions: Global glomerulosclerosis and segmental sclerosis might be used for management and treatment of adult-onset IgAV-N.